A case report of pregnant mother death due to severe DIC caused by a scorpion sting - Zohreh Mirkazehi; Masoumeh Mobaraki; Atefeh Shohlibor; Firouzeh Sheikhi; Mohamad Dokali; Bibi Maryam Mirlashari (Mashhad University of Medical Sciences, 2023)
Introduction: Scorpion bite is an important health issue that in many cases occurs in Sistan and Baluchistan province. Severe complications of scorpion bite include: decreased renal blood flow, renal failure, severe hemolysis, pancreatitis, hepatitis, DIC, miscarriage, and death. In this study, a case of mother's death due to DIC caused by scorpion bite is reported. Case presentation: A 19-year-old primigravid woman with the gestational age of 33 weeks, 5 days after being bitten by a scorpion, following a decrease in the level of consciousness with GCS: 3/15, intubation,undergoing blood transfusion was transferred from Rusk Hospital and admitted to the ICU ward. After being sent to Iranshahr, the patient was examined by anesthesiologist and gynecologist. In the examinations, severe lung rales were heard and bruises caused by scorpion bite were observed on the left side. In ultrasound, a fetus without heartbeat, biliary edema and hydronephrosis were evident. Induction and antiserum treatment started for scorpion stings. Four hours later, mother suddenly had bradycardia and asystole, CPR was performed and despite 45 minutes of CPR, the patient died. Conclusion: In this patient, due to delay in transferring her to the medical center caused the doctors to fail to save her in time. If the patient bitten by scorpion does not come to hospital within the first 6 hours, she will lose the chance of treatment, and if the more time passes, she will face the risk of death due to the infiltration of poison into the bloodstream, so a person bitten by scorpion should refer to the hospital at the first opportunity and special tests should be performed.